ECONOMIC BIOLOGY AND BEHAVIORAL ECONOMICS the prophesy of alfred marshall. - Cory, Gerald A. ([S.l.] : ROUTLEDGE, 2022)
Economic Biology and Behavioral Economics: The Prophesy of Alfred Marshall explores the prophesy of Alfred Marshall, the grand synthesizer of neoclassical economics, that the "Mecca of the economist lies in economic biology". The book presents the proof of that prophesy through examination and establishment of the fundamental biological science necessary and then applying that science to the examination of current economic theory. In doing so, the book focuses primarily on the fundamentals of neoclassical economic theory-- which is the reigning theory and the general framework of which is taught as "science" in first courses in college economics. These courses are at best an idealization, if not an ideology, of the discipline--presented to fresh minds misleadingly as confirmed science. The book examines the bases and the history of these idealizations, points to the sources of their error from the biological perspective and suggests a path forward for the discipline. Through this process, the book demonstrates the power of the biological perspective anticipated by Marshall. This book provides invaluable reading for anyone interested in the future of economics and economic theory, and particularly those interested in behavioral economics and neuroeconomics.
Keywords: Neoclassical school of economics; Science -- Methodology; Biology, Economic; Neuroeconomics; BUSINESS & ECONOMICS / Economic History; BUSINESS & ECONOMICS / Economics / General